False.
Let's analyze the expression step by step. The expression \((2^3)^{-3}\) should be simplified as follows:
-
Use the power of a power property: \((a^m)^n = a^{m \cdot n}\). \[ (2^3)^{-3} = 2^{3 \cdot (-3)} = 2^{-9} \]
-
Rewrite \(2^{-9}\) using the negative exponent rule: \(a^{-n} = \frac{1}{a^n}\). \[ 2^{-9} = \frac{1}{2^9} \]
-
Calculate \(2^9 = 512\). \[ 2^{-9} = \frac{1}{512} \]
Therefore, the correct simplified form is \(2^{-9} = \frac{1}{512}\), and the work shown in the question is incorrect. Thus, the answer is False.